Nervenschwäche und Krieg Modernitätskritik und Krisenbewältigung in der Österreichischen Psychiatrie (1880-1920) - Hofer, Hans-Georg (2004)
Since the 1880s neurasthenia - a term popularised by New York-physician George Beard - was discussed an a phenomenon of modernity, but over a long period of debate, psychiatry were not able to define what this "modern malady" exactly meant nor was it able to find any discernible causes for the epidemic disease. Neurasthenia was not simply a diagnostic term, which was often applied by fin de siècle-physicians to their workaday routine, but a kind of lifestyle, a sign of a certain emotional sensitivity in modern times. In the last decade historical research on neurasthenia has focused on Britain, Germany and the Netherlands. But what happened in Austria-Hungary, especially in Vienna? Focusing on Viennese psychiatry, part one of the book analyses the "invention" of Neurasthenia and the adoption of Beards thesis in Austrian medicine, bringing out various figures and alternative methods of explanations of the disease that was identified as a central, yet unwanted feature of modern manliness. Based on this the outcome of war could be seen as an instance of 'nerve-corrections'. Like many medical professionals in Austria-Hungary, psychiatrists had reacted to the war with nearly unanimous support: patriotic habits went hand in hand with high psychiatric expectations of the powerful mental effects of war. These hopes were badly disappointed. In the more recent literature on the medical and cultural history of the Great War, the phenomenon of the epidemic mental breakdowns of soldiers has been given a prominent place. 'Shellshock' and 'war neurosis' are now key words and frequent metaphors for the shattering effects of an industrialized war. In a sense these psychiatric labels symbolically represent the destructive impact of mechanized weapons on body and soul, the loss of narrative structures and the traumatic after-effects of modern warfare. How can Viennese-centred Austrian psychiatry in the First World War be characterized? With regard to new studies on the history of trauma, war and psychiatry I intend to emphasize two interpretations. Firstly, as in German and other European psychiatric war communities, models of rationalisation and modernisation are of significance when focusing on this topic. Viennese psychiatrists were neither particularly brutal nor especially tolerant in the way they dealt with the situation. Instead, as in other European countries in the Great War, they acted in keeping with military requirements and standards. Secondly, the specific political and cultural context of the Austro-Hungarian situation is of utmost importance as well. Shell-shock was a phenomenon that affected all nations, but reactions differed according to different national traditions and different medical ways of understanding, representing and acting. In a comparative cultural history of World War One, Austria-Hungary is a model of a shattered society, paralysed by ethnic conflicts and cultural differences. In this context, the therapeutic response to war neurosis was affected by language confusion, national stereotypes and malingering. The German-Austrian psychiatrists not only emerged as a group of experts who had taken responsibility for the efficient treatment of war neurosis, but also as a pressure group that intended to keep centrifugal forces of the multinational empire under control.